Regulation of gene expression by repression condensates during development - Treen, Nicholas; Shimobayashi, Shunsuke F.; Eeftens, Jorine; Brangwynne, Clifford P.; Levine, Michael S. (bioRxiv, 2020)
There is emerging evidence for transcription condensates in the activation of gene expression1–3. However, there is considerably less information regarding transcriptional repression, despite its pervasive importance in regulating gene expression in development and disease. Here, we explore the role of liquid-liquid phase separation (LLPS) in the organization of the Groucho/TLE (Gro) family of transcriptional corepressors, which interact with a variety of sequence-specific repressors such as Hes/Hairy4. Gro-dependent repressors have been implicated in a variety of developmental processes, including segmentation of the Drosophila embryo and somitogenesis in vertebrates. These repressors bind to specific recognition sequences, but instead of interacting with coactivators (e.g., Mediator) they recruit Gro corepressors5. Gro contains a series of WD40 repeats that are thought to mediate oligomerization6. How putative Hes/Gro oligomers repress transcription has been the subject of numerous studies5, 6. Here we show that Hes/Gro complexes form discrete puncta within nuclei of living Ciona embryos. These puncta rapidly dissolve during the onset of mitosis and reappear in the ensuing cell cycle. Modified Hes/Gro complexes that are unable to bind DNA exhibit the properties of viscous liquid droplets, similar to those underlying the biogenesis of P-granules in C. elegans7 and nucleoli in Xenopus oocytes8. These observations provide vivid evidence for LLPS in the control of gene expression and suggest a simple physical exclusion mechanism for transcriptional repression. WD40 repeats have been implicated in a wide variety of cellular processes in addition to transcriptional repression9. We suggest that protein interactions using WD40 motifs might be a common feature of processes reliant on LLPS.